2014
DOI: 10.1117/12.2045164
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of an optically pumped metastable Ar laser

Abstract: In recent studies, an optically pumped Ar*/He laser has been demonstrated using the Ar 4p[1/2] 1 →4s[3/2] 2 transition at 912.55 nm. Time-resolved data for this system, recorded using CW laser excitation and pulsed discharge production of Ar* 4p[3/2] 2 , yielded laser output pulses that were of unexpectedly short duration. It was speculated that radiative relaxation from the upper laser level to the 4s[3/2] 1 state (607 cm -1 above 4s[3/2] 2 ) caused termination of the laser pulse. In the present study this hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 9 publications
0
13
1
1
Order By: Relevance
“…[1][2][3] The inversion follows a basic three-level scheme, wherein the metastable 3 P J rare-gas atoms (e.g. Ar(4s)), generated in an electric discharge, are optically excited to an upper state, undergo collisional energy transfer to a state at slightly lower energy to produce the inversion, and lase back to the metastable state.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] The inversion follows a basic three-level scheme, wherein the metastable 3 P J rare-gas atoms (e.g. Ar(4s)), generated in an electric discharge, are optically excited to an upper state, undergo collisional energy transfer to a state at slightly lower energy to produce the inversion, and lase back to the metastable state.…”
Section: Introductionmentioning
confidence: 99%
“…The optically pumped rare-gas metastable laser (OPRGL) is an attractive means for efficient conversion of high-power diode laser output into gas laser output with high beam quality, at a variety of near-infrared wavelengths [1][2][3]. The mechanism for population inversion follows a basic three-level scheme, wherein the metastable 3 P J rare-gas atoms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…First we study the influence of 21 k , the collisional relaxation rate from 4 1s to 5 1s . Jiande Han et al found that the relatively low value of 21 k may form a bottleneck in atomic cycling process, thus decrease the laser efficiency [14]. Our simulation results are shown in Fig.…”
Section: Theoretical Study Of Characteristics Of Oprglmentioning
confidence: 75%
“…The radiative decay to 4 1s , 3 1s and 2 1s accounts for 21.8%, 0.6% and 3.6% of the total decay rate of 10 2p . A relatively low collisional relaxation rate of 4 5 1 1 → s s may form a bottleneck in the population cycling process [14]. (2) The population in upper pump ( 9 2p ) and laser ( 10 2p ) levels could be further collisionally relaxed into higher levels by endothermic processes, especially to the 8 2p level, which subsequently radiates to the 5 1s , 4 1s and 2 1s states.…”
Section: Theoretical Model Of Oprglsmentioning
confidence: 99%
See 1 more Smart Citation